P05.02 A phase I/IIa dose escalation study evaluating the safety and efficacy of autologous CD34+ enriched hematopoietic progenitor cells genetically modified for human interferon-α2 in patients with GBM and an unmethylated MGMT promoter (TEM-GBM-001). (6th September 2019) - Gentner, B; Ciceri, F; DiMeco, F; Legnani, F; Eoli, M; Pollo, B; Farina, F; Mazzoleni, S; Russo, C; Naldini, L; Finocchiaro, G
Abstract: BACKGROUND: Glioblastoma (GBM) remains the most common malignant primary brain tumor in adults. Most patients with GBM & an unmethylated O-6-methylguanine-DNA methylase (MGMT) gene promoter, have a poor prognosis with approximately 20% of patients surviving to 2 years. Poor prognosis is likely related to a number of factors including a highly immunosuppressive tumor microenvironment (TME). The TME in GBM is mainly composed of tumor associated macrophages (TAMs) & microglia. A subset of tumor-infiltrating macrophages characterized by expression of the angiopoietin receptor Tie2 (TEMs) have features of M2-TAMs, promote tumor angiogenesis & are infrequently found in normal organs. Tie2 is significantly upregulated upon homing to tumors. Gene therapy technology has allowed TEMs to be used as carriers for the local and tumor restricted release of interferon-α (IFN). IFN has antitumor effects, inhibits angiogenesis & modulates the immune system. Cell-based delivery of IFN into the TME by TEMs is expected to provide efficacy, taking advantage of pleiotrophic anti-tumor effects & avoiding tolerability issues associated with systemic IFN treatment. MATERIAL AND METHODS: We are currently conducting a Phase I/IIa clinical study in Milan to evaluate this therapeutic approach (Temferon) in 21 patients with GBM & unmethylated MGMT promoter (EudraCT Number 2018- 001404-11). The study recruits & follows up patients at a specialist neurosurgical & neuro-oncology unit (INCB); administration of Temferon & hematological follow up takes place at a specialist hematology & bone marrow transplantation unit at OSR. Potentially eligible patients are identified immediately after first surgical resection of GBM once the MGMT promoter methylator status is known. Once screening procedures have been completed, harvesting of HSPCs occurs followed by 6 weeks of radiotherapy. Patients receive a non-myeloablative conditioning regimen consisting of BCNU & thiotepa. This is followed by administration of non-manipulated HSPCs and Temferon. In-patient monitoring occurs until hematological recovery. Thereafter, regular follow-up of patients occurs up to 2 years (+720 days) and patients will be invited to participate in a long term follow-up study lasting an additional 6 years. RESULTS: In Part A of the study, 3 cohorts of 3 patients will receive escalating doses of Temferon. On completion of Part A, a single dose of Temferon will be selected to be studied in a further 12 patients in Part B. Criteria for study eligibility are the same for both Part A and Part B. In the event that GBM disease progression occurs, patients will be managed with second line therapies including second surgery, TMZ, BCNU, fotemustine or any other approved therapy for GBM. Patient recruitment for Part A is ongoing with the first dose of Temferon administered in July 2019.